Visualizing Proteasome Activity and Intracellular Localization Using Fluorescent Proteins and Activity-Based Probes - Schipper-Krom, Sabine; Sanz, Alicia Sanz; van Bodegraven, Emma J.; Speijer, Dave; Florea, Bogdan I.; Ovaa, Huib; Reits, Eric A. (Frontiers in Molecular Biosciences, 2019)
Proteasomes are the main proteases in the cell, responsible for the turnover of most cytoplasmic and nuclear proteins. They are essential for many cellular processes and various diseases are associated with altered proteasome activities and even malfunctioning. Proteasome activity depends on the nature of the catalytic subunits, which are interchangeable, as well the interaction with associated proteasome activators. Here we describe various methods to study proteasome functioning in living cells, using different fluorescently-tagged proteasome subunits and activity-based proteasome probes to study proteasome localization and dynamics, activity and association with proteasome activators.